2013
DOI: 10.1371/journal.pone.0078609
|View full text |Cite|
|
Sign up to set email alerts
|

Uganda's New National Laboratory Sample Transport System: A Successful Model for Improving Access to Diagnostic Services for Early Infant HIV Diagnosis and Other Programs

Abstract: IntroductionUganda scaled-up Early HIV Infant Diagnosis (EID) when simplified methods for testing of infants using dried blood spots (DBS) were adopted in 2006 and sample transport and management was therefore made feasible in rural settings. Before this time only 35% of the facilities that were providing EID services were reached through the national postal courier system, Posta Uganda. The transportation of samples during this scale-up, therefore, quickly became a challenge and varied from facility to facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
86
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 3 publications
1
86
0
Order By: Relevance
“…The Kampala laboratory, depending on sample transport to improve efficiency, began operations in July 2011 and a National Sample and Results Transport Network (NSRTN) later that year. 30 Local networks based at hospitals serve as hubs for all health facilities within a defined catchment area (30-40 km radius). The MoH allotted each hub a motorbike and funds to employ a rider to make (at least) weekly scheduled sample pickups from all its facilities.…”
Section: Redesign Decision and Steps To Consolidate The Eid Laboratormentioning
confidence: 99%
See 1 more Smart Citation
“…The Kampala laboratory, depending on sample transport to improve efficiency, began operations in July 2011 and a National Sample and Results Transport Network (NSRTN) later that year. 30 Local networks based at hospitals serve as hubs for all health facilities within a defined catchment area (30-40 km radius). The MoH allotted each hub a motorbike and funds to employ a rider to make (at least) weekly scheduled sample pickups from all its facilities.…”
Section: Redesign Decision and Steps To Consolidate The Eid Laboratormentioning
confidence: 99%
“…The transport network assured rapid delivery of samples to the high-tech EID laboratory from every health facility in the county. [30][31][32] Evaluating Achievements and Challenges in 2012…”
Section: Redesign Decision and Steps To Consolidate The Eid Laboratormentioning
confidence: 99%
“…Transportation of samples and relays of test results to and from remote treatment centers and reference laboratories is challenging and costly. Recently, Kiyaga et al reported how Uganda's new coordinated sample transport model increased access to EID services from 36% to 51% [74]. The system significantly reduced transportation costs by 62%, reduced turnaround time by 46.9%, and by a further 46.2% by introducing SMS printers [74].…”
Section: Sample Collection and Transportationmentioning
confidence: 99%
“…Recently, Kiyaga et al reported how Uganda's new coordinated sample transport model increased access to EID services from 36% to 51% [74]. The system significantly reduced transportation costs by 62%, reduced turnaround time by 46.9%, and by a further 46.2% by introducing SMS printers [74]. Improvising near-efficient transport systems and the scale-up of DBS may significantly improve access to laboratory services and HIV care in sub-Saharan countries.…”
Section: Sample Collection and Transportationmentioning
confidence: 99%
“…This innovation was later enhanced by the introduction of the national hub-and-spoke system for DBS sample collection and transport from a network of health facilities to a lab hub from where samples were delivered to the central EID laboratory using the Posta Uganda courier services [11]. EID for exposed infants is not a one off test, but a series over time (6wks to 18months).…”
mentioning
confidence: 99%